Pengaruh Pendekatan Situasional Dalam Kepemimpinan Pendidikan - Mustika, Dea; Wulandari, Aliza; Cahyati, Dwi Surma; Rofah, Gusrika Fauza; Khoirunnisa, Khoirunnisa; Safitri, Melinia; Hussaidah S, Miftah; Chaniago, Yovanes (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of writing this article is to describe the effect of using a situational approach inleadership style. The writing of this article uses the literature study method. Any informationobtained by reviewing national research journals as well as books and other sources relevant toleadership style. The stages that were passed in writing this article: 1) Looking for literaturesources relevant to the topic of the article; 2) Analyze the information obtained; 3) Summarizingand developing the results from each literature. The results of the analysis show that thesituational approach to leadership style can build the readiness of teachers and education staff incarrying out the duties and obligations of the learning process in schools, by empathizing with the existing situational leadership style. The use of the four appropriate situational leadership stylescan make a person with his leadership more effective and directed in accordance with educational goals.